Pengembangan Media Pembelajaran PAI berbasis PowerPoint di SMA Plus Misbahul Khair - Habibah Amumpuni; Nur Ani Parida; Hariyati Hariyati; Ferlian Nur Alif Prayoga; Dessy Kurnia Mulyani (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
The development of instructional media encompasses all tools that can be developed to assist teachers in delivering messages to students, thereby creating a clearer, engaging, efficient, and effective learning process. The aim of this research is to understand the development of instructional media in Islamic Education (Pendidikan Agama Islam or PAI) focusing on PowerPoint. The research method employed is qualitative with a field study conducted at SMA Misbahul Khair, South Kotabumi, North Lampung. The results of this study indicate that the development of learning media based on PowerPoint for the subject of Islamic Education has a positive and responsive impact on class XI students at Misbahul Khair High School. The material, which was previously somewhat abstract due to a reliance on textual explanations, becomes more concrete and easily comprehensible when presented using PowerPoint, directly aiding students' understanding.